GameStop Capitalism. Wall Street vs. The Reddit Rally (Part I) - Tim Di Muzio (The Bichler and Nitzan Archives, 2021)
Reflections on leveraging finance against finance.
Keywords: G; P16; 330; capital as power; finance; hype; stock market